Interactions of nitrogen and phosphorus cycling promote P acquisition and explain synergistic plant‐growth responses. Issue 5 (17th March 2020) - Schleuss, Per Marten; Widdig, Meike; Heintz‐Buschart, Anna; Kirkman, Kevin; Spohn, Marie
Abstract: Plant growth is often co‐limited by nitrogen (N) and phosphorus (P). Plants might use one element to acquire another (i.e., trading N for P and P for N), which potentially explains synergistic growth responses to NP addition. We studied a 66‐yr‐old grassland experiment in South Africa that consists of four levels of N addition with and without P addition. We investigated the response of aboveground net primary production (ANPP) to N and P addition over the last 66 yr. Further, we tested whether phosphatase activity and plant P uptake depend on N availability, and vice versa, whether non‐symbiotic N2 fixation and plant N uptake depend on P availability. We expected that the interaction of both elements promote processes of nutrient acquisition and contribute to synergistic plant growth effects in response to NP addition. We found synergistic N and P co‐limitation of ANPP for the period from 1951 to 2017 but the response to N and P addition diminished over time. In 2017, aboveground P stocks, relative rRNA operon abundance of arbuscular mycorrhizal fungi, and soil organic P storage increased with N fertilization rate when N was added with P compared to the treatment in which only N was added. Further, N addition increased phosphatase activity, which indicates that plants used N to acquire P from organic sources. In contrast, aboveground N stocks and non‐symbiotic N2 fixation did not change significantly due to P addition. Taken together, our results indicate that trading N for P likely contributes to synergistic plant‐growth response. Plants used added N to mobilize and take up P from organic sources, inducing stronger recycling of P and making the plant community less sensitive to external nutrient inputs. The latter could explain why indications of synergistic co‐limitation diminished over time, which is usually overlooked in short‐term nutrient addition experiments.